2014
DOI: 10.1007/s00405-014-2935-4
|View full text |Cite
|
Sign up to set email alerts
|

Brush biopsy with DNA-image cytometry: a useful and noninvasive method for monitoring malignant transformation of potentially malignant oral disorders

Abstract: Oral and pharyngeal cancer is the sixth most common cancer worldwide, the 5-year survival rate has not yet increased. A key factor in rates not having improved is the lack of early detection. This study was undertaken to estimate the diagnostic accuracy of brush biopsy with DNA-image cytometry (a noninvasive method) for potentially malignant oral disorders compared with tissue biopsy pathology in China. Exfoliative cells were obtained using a cytobrush cell collector from oral mucosa of 52 subjects, followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…Although previous studies have reported that brush biopsies are problematic for general OPC screening because they cannot directly sample tumors arising in tonsillar crypts [ 7 ], brush biopsies of clearly visible and accessible OPC lesions have been reported to be effective for HPV detection [ 7 , 42 ]. Further, brush biopsies in the adjacent oral cavity, where tissues are less convoluted, have been reported to have high sensitivity and specificity for the detection of DNA aneuploidy, a nuclear morphological marker of neoplastic cell transformation [ 43 ]. Thus, the identification of MACs in surface epithelium represents the initial step towards the development of a brush biopsy-based screening method for early-stage oropharyngeal tumors in high-risk populations.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have reported that brush biopsies are problematic for general OPC screening because they cannot directly sample tumors arising in tonsillar crypts [ 7 ], brush biopsies of clearly visible and accessible OPC lesions have been reported to be effective for HPV detection [ 7 , 42 ]. Further, brush biopsies in the adjacent oral cavity, where tissues are less convoluted, have been reported to have high sensitivity and specificity for the detection of DNA aneuploidy, a nuclear morphological marker of neoplastic cell transformation [ 43 ]. Thus, the identification of MACs in surface epithelium represents the initial step towards the development of a brush biopsy-based screening method for early-stage oropharyngeal tumors in high-risk populations.…”
Section: Discussionmentioning
confidence: 99%
“…As Souto et al, the presence of aneuploidy could be attributed to the cell degeneration found in the superficial layer of the epithelium. Nevertheless, according to Ma et al, it should be considered that the DNA content analysis in exfoliated cells can yield false‐positive results in some cases due to the overlapping cells and the presence of an inflammatory exudate and necrotic cells. The authors reported false‐positive and false‐negative rates of 13.64% and 10%, respectively, in 52 cases of intraoral lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The following step to progression may lead to aneuploidy with oral potentially malignant disorders, which can undergo transformation to oral squamous cell carcinoma (SCC) . The analysis of DNA content is a useful tool to study and predict the behavior of oral malignant lesions and their precursors . Aneuploidy indicates the loss or acquisition of one or more chromosomes, events that affect the total DNA content of a cell …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the study of Bisht et al ( 23 ) reported that certain minor changes and chromosomal abnormalities cannot be detected by DNA analysis. When the number of diploid cells predominates over that of heteroploid cells, DNA analysis may still not detect abnormal cells ( 21 , 30 ). In addition, DNA quantitative analysis does not reveal heteroploid cells if the tumor chromosomes maintain a balance between loss and replication ( 18 , 31 ).…”
Section: Discussionmentioning
confidence: 99%